Local Problems on the Coasts of Istanbul: Maltepe-Kartal Coastline - Berrak Kırbaş Akyürek (Megaron, 2019)
Public open spaces in the coastal areas constitute important part of the recreational areas in İstanbul. These green spaces are a few of the limited activity areas where people may relax in the hectic and chaotic metropolitan life. However, the ever-increasing population and rising constructions threaten the future of the coasts of İstanbul. Despite the potential of Marmara Sea as bringing visual and tangible interaction with water, unused and unwelcome recreational areas in coastline where people cannot perform any activity neither on land nor on sea are in the danger of destruction and privatization. This paper aims to underline opportunities and treats that effects user inclusiveness in the recreational areas in the coasts of Istanbul with a research on user's requests and suggestions in Maltepe-Kartal Coastline. At this juncture, having picnic comes out as a local and critical problem, since air and environmental pollution caused by barbecue and the smoke affect the use of the space for different activities by different users. Although this problem reduces the user inclusiveness, it is rarely discussed in the existing literature, and mainly ignored in the planning and design process. In the scope of the work, the ideas of the users from opposite views are gathered together in the framework of judgmental sample technique by using survey and interview method. Consequently, the findings obtained from the participation of users from different point of views and experiences on the place highlight that the recreation areas in the coasts of İstanbul should be designed and planned by bringing solution to the local problems.